La questione degli Archivi sabaudi tra Italia e Francia: un auspicio - Vedovato, Giuseppe (Rivista di studi politici internazionali, 2011)
The transfer of the Savoy’ Archives from Italy to France, followed on from the Peace Treaty in 1947, constituted a loss of documents and historical heritage. The files indeed showed the tendency of the Savoia Monarchy, since the Middle Age, towards the organization and modernization of the State institutions. In 1430, Amedeo VIII organized the Archives with the new Statutes Law. Then in 1720 Vittorio Amedeo II began rationally the reunion of the funds in Turin. In 1731, the architect Filippo Juvarra planned a new place, connected with the royal palace and the Government. The French and Napoleonic domination implicated damages and dispersion of the Archives, so that after 1814 they needed a new, complicated arrangement. In 1860 with the transfer of Savoy to France, despite agreements, there were difficult relationships about the management of the Archives. In the same year a mixed Committee promulgated article 10 of the French-Sardinian Convention, but the disputes didn’t end. In 1866 a new attempt of agreements predisposed same concessions, nevertheless many incomprehensions remained irresolved. In the Thirties of the XX century, thanks to other concessions, the researchers realized the important inventories. Then, after the lost war, the Archives in Turin were dispersed, but some important historical files were filmed, as the pages of Camera dei Conti. The 150th anniversary of the Italian unification is an occasion not to be lost. The Author wishes the reunion of the files, in the name of Europe. La cession italienne des archives de la Savoie, en 1947, après le traité de paix, a été une perte en termes de matériel archivistique et de mémoire historique. En effet, les Archives de la Savoie montraient la tendance de la Monarchie ducale, depuis le Moyen Âge, à l’organisation et à la modernisation des institutions judiciaires et administratives. En 1430, Amedeo VIII avait ordonné l’organisation rationnelle des archives ainsi que de elaborer les statuts; depuis 1720, Vittorio Amedeo II voulait la recomposition organique des fonds d’archive dans la cité de Turin. En 1731,1’architecte Filippo Juvarra a conçu un nouveau bâtiment, relié au Palais royal; de cette façon, les Archives ont été encore plus utiles à l’administration centrale. Par la domination française du Piémont, puis par 1’annexion napoléonienne de cette province, s’ouvre une nouvelle période dans la vie des Archives: dommages et déplacement de documents. En 1860, avec le passage de la Savoie à la France, il y avait des accords, mais il y eut des problèmes. Une commission mixte, en 1860, prépara l’article 10 de la convention entre la Sardaigne et la France, mais cela ne mit pas fin aux disputes. En 1866, une nouvelle tentative d’accord ne permit que quelques concessions. Des incompréhensions restèrent, ainsi que des ouvertures aux spécialistes, ouvertures qui permirent de réaliser des importants inventaires dans les années trente. La guerre perdue imposa à l’ltalie le démembrement des fonds gardés à Turin, même si quelques pertes furent rémunerées par le microfilmage de fonds importants comme ceux de la Chambre des Comptes. L’Auteur invite à faire des 150 ans de l’Unité italienne l’occasion par réunir les Archives à Turin, au nom de l’Éurope.PAROLE CHIAVE: Archivi storici; Archivio di Stato di Torino; Savoia (Casa regnante); Rapporti Italia-Francia; Regno di Sardegna.